Robust increase in South Asian monsoon rainfall under warming driven by extratropical clouds and ocean - Yong-Jhih Chen; Yen-Ting Hwang; Jian Lu (npj Climate and Atmospheric Science)
Abstract The responses of South Asian Monsoon (SAM) circulation under global warming are known to be highly uncertain, leading to the widespread of SAM rainfall projections among models. Here, we show that the uncertain SAM circulation in Coupled Model Intercomparison Project Phase 6 models consists of two robust components that partly offset each other: a weakening component linked to a global thermodynamic constraint and a northward shift component understood through a regional 2D energetic perspective. We further attribute the robust northward shift of SAM circulation to positive cloud feedback over the Eurasia Continent and heat uptake in the Southern Ocean. A set of climate model simulations supports the finding that SAM rainfall increase is primarily due to the northward shift of circulation driven by extratropical processes. This energetic perspective opens new avenues for predicting monsoon rainfall by connecting circulation changes to radiative forcing, feedbacks, and ocean heat uptake.